Technology for Smart Futures (Springer International Publishing, 2018)
This book explores the nexus of Sustainability and Information Communication Technologies that are rapidly changing the way we live, learn, and do business. The monumental amount of energy required to power the Zeta byte of data traveling across the globe's billions of computers and mobile phones daily cannot be overstated. This ground-breaking reference examines the possibility that our evolving technologies may enable us to mitigate our global energy crisis, rather than adding to it. By connecting concepts and trends such as smart homes, big data, and the internet of things with their applications to sustainability, the authors suggest that emerging and ubiquitous technologies embedded in our daily lives may rightfully be considered as enabling solutions for our future sustainable development.